Does Economic Crisis Always Harm International Migrants? Longitudinal Evidence from Ecuadorians in Barcelona. (18th March 2013) - Moser, C. O. N.; Horn, Philipp
Abstract Current research on the impacts of the 2007 global economic crisis on international migration takes two different positions. Some studies emphasize the negative impacts while others are more positive. This article argues that these two positions offer simplistic interpretations which fail to take account of the complex micro‐level realities that determine migrant experiences. The article discusses how a small group of migrants from Guayaquil, Ecuador, accumulate and consolidate a complex portfolio of assets both before and during the economic crisis in Spain. Conceptualized in terms of an asset accumulation framework, and based on micro‐level longitudinal trend data, rather than the more generally used macro‐level snapshots or anecdotal evidence, the study highlights the fact that the formalization of legal status or citizenship is a crucial pre‐condition, which sets in motion a 'virtuous' cycle of consolidation of an interrelated portfolio of assets, regardless of the wider macro‐economic environment. Even if this turns into a 'vicious' cycle, for those losing jobs, to date Spanish welfare benefits have acted as a social protection mechanism.